EFL Learners’ Opinion on Difficulties in Pronouncing English Sounds - Kurnia Budiyanti; Ibrahim, Nelvia (Jadila: Journal of Development and Innovation in Language and Literature Education, 2025)
This study investigated the students’ opinion on difficulties in pronouncing English sounds. The study employed a quantitative method with survey research design. Approximately 90 students of the third semester of English Education Department participated to answer a questionnaire which included the pronunciation features and the factors that affect the problem. The data collected were analyzed by employing descriptive analysis. The results indicated that the third semester students of English Education Department had negative opinion in pronouncing English sounds. The difficulties involved vowels, consonants, stress, and intonation. Related to factors that affect pronunciation, the findings revealed that native language was the most dominant factor compared with others. It could be concluded that pronouncing English sounds became a problem of the students due to different phonological system. These research findings have implication for learners to be aware of specific pronunciation challenges. Moreover, teachers also need to adopt phonetics-based approaches in teaching process. Further study could investigate research that explore more on research samples, research design, and instruments to gain more specific results.